2006
DOI: 10.1007/s10886-006-9127-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Communication in Chagas Disease Vectors. Source, Identity, and Potential Function of Volatiles Released by the Metasternal and Brindley's Glands of Triatoma infestans Adults

Abstract: Compounds from the metasternal and Brindley's glands of the blood-sucking bug, Triatoma infestans, were identified by solid phase microextraction (SPME) and gas chromatography-mass spectrometry. Volatile compounds released by adult bugs during copulation or after mechanical disturbance were also characterized. Six compounds were identified and found consistently in all samples from metasternal glands. The most abundant were 3-pentanone, 2-methylbutanol, 3-pentanol, and an unidentified compound. The metasternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 25 publications
7
109
1
Order By: Relevance
“…It should be mentioned that isobutyric acid has also been identified as a main constituent of the alarm pheromone of triatomines (e.g. Cruz López et al 1995, Guerenstein and Guerin 2004, Manrique et al 2006, Rojas et al 2002, Schofield 1979a. Thus, a parsimonious use of this odorant by these insects has been proposed (Guerenstein and Guerin 2001, Guerenstein and Lazzari 2009) because it is used by triatomines as, at least, host attractant and alarm signal depending on its concentration, sensory (in particular odour blend) context and the physiological state of the perceiving bug.…”
Section: Olfaction In Vector-host Interactions 315 14 the Role Of Olmentioning
confidence: 99%
“…It should be mentioned that isobutyric acid has also been identified as a main constituent of the alarm pheromone of triatomines (e.g. Cruz López et al 1995, Guerenstein and Guerin 2004, Manrique et al 2006, Rojas et al 2002, Schofield 1979a. Thus, a parsimonious use of this odorant by these insects has been proposed (Guerenstein and Guerin 2001, Guerenstein and Lazzari 2009) because it is used by triatomines as, at least, host attractant and alarm signal depending on its concentration, sensory (in particular odour blend) context and the physiological state of the perceiving bug.…”
Section: Olfaction In Vector-host Interactions 315 14 the Role Of Olmentioning
confidence: 99%
“…This ample knowledge reported by the authors indicates that the development of sampling or detection devices can be based on solid information. Other aspects of triatomine behaviour, such as aggregation and sexual signals, are being studied and may generate further alternatives for interfering with insect communication processes and manipulating their behaviour (Lorenzo et al 2000, Manrique et al 2006, Pontes et al 2008.…”
Section: Biology Diversity and Strategies For The Monitoring And Conmentioning
confidence: 99%
“…92 Behavioral studies suggested both an alarm and defensive role of these compounds. 91,92 Several short-chain ketones and alcohols were also detected in the metasternal glands of adult female R. prolixus, and a possible role in sexual communication of the species was suggested. …”
Section: Assassin Bugs (Hemiptera: Reduviidae)mentioning
confidence: 98%
“…The role of Brindley's and metasternal glands in chemical communication of T. infestans has been studied 90 and it has been suggested that volatiles released from the metasternal glands are involved in sexual and alarm behavior of this species. 90,91 Several compounds have been identified from metasternal glands, including 3-pentanone, 2-methylbutanol, and 3-pentanol. 91 Major volatiles released from Brindley's glands include isobutyric acid, 2-methylbutanol, 3-methylbutanol 91 as well as the isobutanoates of the latter alcohols.…”
Section: Assassin Bugs (Hemiptera: Reduviidae)mentioning
confidence: 99%
See 1 more Smart Citation